(untitled) (Research, Society and Development, 2021)
The aim of this review is to explore the potentials existing in insecticides that are considered Insect Growth Regulators (IGR) for the control of insects considered crop pests, with an observation of the main mechanisms of neuroendocrine modifications, development and viability of the species used as study models. The data search on digital platforms, as well as the screening of materials about crop pests, resulted in 74 IGR references and their potentials. The analysis of the information found demonstrated a greater use in works of compounds belonging to chitin synthesis inhibitors class; and orders such as Hemiptera, Lepidoptera, Coleoptera, Orthoptera, Thysanoptera and Diptera were represented in the studies. The main types of activities reunited were morphological and anatomical modifications, reproductive modifications, alterations in developmental stage, alterations in developmental period, ovicidal activity, larvicidal/ninficidal activity and fagoinhibition. The congregated knowledge about the main pests used as study models, the main IGRs compounds and their biological potentials allow an evaluation of their use as an informative source for crop pest control methods.